THE EFFECT OF PROFITABILITY AND MANAGERIAL ABILITY ON EARNINGS QUALITY WITH AUDIT QUALITY AS A MODERATING VARIABLE: EVIDENCE FROM INDONESIA - Benedictus J P Soendjojo; William Tjong (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study examines the impact of profitability and managerial ability on earnings quality, with audit quality as a moderating variable. Using a sample of 204 firm-year observations from industrial sector companies listed on the Indonesia Stock Exchange (2021–2024), this research applies multiple linear regression and moderation analysis. The findings reveal that profitability and managerial ability have significant negative effects on earnings quality. Additionally, audit quality does not significantly moderate these relationships. These results suggest that higher profitability and managerial efficiency may incentivize earnings management practices, thereby reducing earnings quality. This study contributes to the literature by highlighting the complex role of internal performance and external audit mechanisms in financial reporting quality.